Revision der paläarktischen Arten der Gattung Mesocrina. 2. Beitrag zur systematischen Bearbeitung der Alysiinae (Hymenoptera, Braconidae). - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1959)
From a study of the types the genus Mesocrina Marshall was found to be heterogenous. The typical species, indagatrix Förster, remaining in the genus Mesocrina, venatrix Marshall is transferred to the new genus Pseudomesocrina (Alysiinae), and pugnatrix Marshall to the new genus Compressaria (Exothecinae). Nomenclatural Acts Compressaria Königsmann, 1959 (Braconidae), gen. n. Pseudomesocrina Königsmann, 1959 (Braconidae), gen. n. pugnatrix (Marshall, 1895) (Compressaria), comb. n. hitherto Mesocrina pugnatrix Marshall, 1895 venatrix (Marshall, 1895) (Pseudomesocrina), comb. n. hitherto Mesocrina venatrix Marshall, 1895